Rwanda : Third Review Under the Policy Coordination Instrument-Press Release; Staff Report; and Statement by the Executive Director and Staff Representative for Rwanda. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
The COVID-19 pandemic is having an adverse impact on Rwanda's economy, despite a sizeable policy response. Output in 2020 is projected to contract by 0.2 percent, compared to an 8 percent increase expected pre-pandemic. The government's early actions helped contain the spread of the virus and mitigate its economic impact, supported by financing from Rwanda's development partners, including from the IMF under the RCF. With the number of infections contained, the authorities are gradually easing up containment measures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet